PERAN UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MENANGANI KRISIS KEMANUSIAAN ANAK DI BURKINA FASO TAHUN 2018-2020 - Gama Atmawijaya; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
International organization the United Nations Children’s Fund (UNICEF) works for reaching vulnerable children with lifesaving nutrition support, health care, and education in the world. The institution was concerned with humanitarian issues for children and the most vulnerable communities. This study elaborated how UNICEF played its roles in settling Burkina Faso children’s rights and providing basic needs as the victims of conflicts in that country. This study used the theory of the role of international organizations from Clive Archer and qualitative research methods with secondary data obtained by analyzing data from books, journals, bulletins, annual reports of several related agencies, documents, or other materials that support the research. The study showed UNICEF working with Humanitarian Action for children could release children in Burkina Faso from all threats in their lives. UNICEF collaboration with the local government and other organizations conducted reconstruction and revitalization efforts successfully. Several activities satisfiedly by UNICEF were providing temporary classrooms for teaching learning activities, conducting campaigns and counseling for wellness, distributing various health and sanitation equipments, and providing psychosocial support. Keywords: Role, UNICEF, Humanitarian Crisis, Children